2013
DOI: 10.1007/s10856-013-5124-x
|View full text |Cite
|
Sign up to set email alerts
|

An exploratory study on the efficacy of rat dedifferentiated fat cells (rDFATs) with a poly lactic-co-glycolic acid/hydroxylapatite (PLGA/HA) composite for bone formation in a rat calvarial defect model

Abstract: In the last two decades, tissue-engineering approaches using scaffolds, growth factors, and cells, or their combination, have been developed for the regeneration of periodontal tissue and bone. The aim of this study was to examine the effects of rat dedifferentiated fat cells (rDFATs) with a poly lactic-co-glycolic acid/hydroxylapatite (PLGA/HA) composite on bone formation in rat calvarial defects. Twenty animals surgically received two calvarial defects (diameter, 5 mm) bilaterally in each parietal bone. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…Mature adipocytes begin to dedifferentiate into elongated non-lipid-filled fibroblast-like cells when cultured in specific conditions such as by using ceiling culture technique [ 4 ] and hydrogels [ 5 ] in vitro . The cells differentiate into multiple cell lineages, including osteoblasts [ 3 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 ], chondrocytes [ 3 , 14 , 16 ], adipocytes [ 3 , 15 , 17 ], myocytes [ 14 , 15 , 18 , 19 , 20 ], and endothelial cells [ 21 ]. Expression markers and proliferative capacity of DFAT cells are analogous to those of MSCs and ADSCs, but are more homogenous [ 3 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Mature adipocytes begin to dedifferentiate into elongated non-lipid-filled fibroblast-like cells when cultured in specific conditions such as by using ceiling culture technique [ 4 ] and hydrogels [ 5 ] in vitro . The cells differentiate into multiple cell lineages, including osteoblasts [ 3 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 ], chondrocytes [ 3 , 14 , 16 ], adipocytes [ 3 , 15 , 17 ], myocytes [ 14 , 15 , 18 , 19 , 20 ], and endothelial cells [ 21 ]. Expression markers and proliferative capacity of DFAT cells are analogous to those of MSCs and ADSCs, but are more homogenous [ 3 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…And it is known that PLGA is inadequate for cell attachment and proliferation 20,21) . There are many factors about surface adsorption of biomaterials, contact angle is often used as an indicator of them.…”
Section: Discussionmentioning
confidence: 99%
“…In the first study that reported the ceiling culture method, a 0.2% collagenase solution was used to isolate mature adipocytes (24). However, other researchers have shown that 0.1% (6), 0.3% (10), 0.2% (25), and 0.075% (26) collagenase can also be used. To the best of our knowledge, there are no studies defining the optimal concentration of collagenase for isolating small adipocytes from BFPs.…”
Section: Effect Of Collagenase Concentration On the Isolation Of Smalmentioning
confidence: 99%